Rol' dliny tonkoy kishki v razvitii sindroma korotkoy kishki - Khasanov, Rasul; Gumerov, A. A.; Wessel, Lucas (Chirurgija, 2017)
Abstract: To define the the role of small bowel length in development of SBS.Seventeen patients with SBS after small bowel resection in neonatal period...
Gesehen am 20.08.2018